Lessons learned from six different structural health monitoring systems on highway bridges. Issue 3 (September 2020) - Peiris, Abheetha; Sun, Charlie; Harik, Issam
Structural health monitoring has been utilized in numerous ways to investigate the performance and integrity of highway bridges. This paper highlights the use of six structural health monitoring systems, which were deployed to monitor distinct behaviors on six bridges in Kentucky. The structural health monitoring systems are as follows: (1) Over-height truck impact detection and monitoring on the I-64 over US 60 bridge, (2) Barge impact detection and monitoring on northbound US 41 over the Ohio River, (3) effectiveness of carbon fiber-reinforced polymer retrofit evaluation based on prestressed concrete I-girder crack movement on the I-65 elevated expressway in Louisville, (4) effect of thermal loads on bridge substructure evaluation on KY 100 over Trammel Creek, (5) thermal movement of expansion joints evaluation on eastbound I-24 over the Tennessee River, and (6) crack growth monitoring on steel floor beam on I-275 over the Ohio River. The deployment of the different structural health monitoring systems on Kentucky bridges has provided valuable insights on their planning, implementation, and maintenance, which can be applied on future structural health monitoring projects. While several of the projects have proved immensely successful, with some still being continuously monitored, others, due to numerous complications, have met with only limited success. The best return on investment was realized from structural health monitoring instrumentation that was focused and limited in scope. The successful structural health monitoring systems had continuous communication between all stakeholders during planning, implementation, and monitoring phases of the projects. Following implementation, the availability of contingency funds through the funding source, to replace/upgrade sensors and networking equipment and costs for reprogramming and reinstallation outside of regular maintenance costs, was also important for the structural health monitoring to be successful.